(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the accountability of Village Fund management as an instrument for improving local economic development in the Sondo Village Government. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The object of the study is the Sondo Village Government with a focus on the practices of planning, implementation, reporting, and accountability of Village Funds and their impact on community economic activities. The research informants numbered 10 people consisting of the Village Head (1 person), Village Secretary (1 person), Finance Head (1 person), Head of Government/Development Section (1 person), BPD members (2 people), BUMDes managers (2 people), and MSME actors (2 people). Informants were selected using a purposive sampling technique, namely based on the consideration that they have knowledge, experience, and direct involvement in the management of Village Funds and local economic development activities in Sondo Village. Data analysis was carried out using an interactive model through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the accountability of Village Fund management in Sondo Village is in the good category, especially in the aspects of transparency, regulatory compliance, and reporting accuracy. These accountability practices have contributed positively to increasing local economic development, as indicated by an increase in the number of micro-enterprises, improvements in economic infrastructure, and a strengthening of the role of Village-Owned Enterprises (BUMDes).